Abundant traveling wave solutions of the compound KdV-Burgers equation via the improved (G′/G)-expansion method - Naher, Hasibun; Abdullah, Farah Aini; Bekir, Ahmet (© 2012 AIP Advances, 2016)
This article was published in the AIP Advances [© 2012 Author(s). ] and the definite version is available at : http://dx.doi.org/10.1063/1.4769751 The Journal's website is at: http://scitation.aip.org/content/aip/journal/adva/2/4/10.1063/1.4769751